Republic of Poland : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report acknowledges the very significant progress achieved by Poland under the leadership of the Ministry of Finance, since publication of the first accounting and auditing ROSC report in July 2002. This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Poland. Companies are required to prepare their financial statements in conformity with Polish accounting requirements, based on the Fourth and Seventh European Union (EU) Company Law Directives, and provide a simplified financial reporting framework for small and medium sized enterprises. Banks are required to prepare their consolidated financial statements in conformity with endorsed International Financial Reporting Standards (IFRS), and their legal entity financial statements in conformity, either with accounting regulations set by the Minister of Finance based on the Banking Accounts Directive, or, with endorsed IFRS. Insurance companies are required to prepare their financial statements in conformity with accounting regulations set by the Minister of Finance based on the Insurance Accounts Directive. Companies listed on the Warsaw Stock Exchange are required to prepare their consolidated financial statements in conformity with endorsed IFRS. This report recommends that public interest entities be required to prepare their consolidated financial statements in conformity with IFRS. Clearly, this measure would go a step ahead of the current requirements of the acquis, as this is not yet required by the EU-other than for the consolidated financial statements of listed companies-however, the ROSC team believes that it would be valuable for enhancing the transparency of financial reporting of public interest entities. This report shows that priorities should now turn to building the monitoring, supervisory, and disciplinary regimes necessary to ensure effective compliance. This assessment demonstrates that the effective enforcement of accounting, auditing and ethical standards is the next challenge that Poland has to tackle. While the report highlights a major program of required reforms to ensure practices catch up with recent regulatory enhancements, the report commends Poland for its achievements to date, some of which go beyond what is presently required by the acquis communautaire and what "peer" large EU Member States are presently doing.